Medical Students' Perspectives on Opportunities to Engage in the Clinical Care of COVID-19 Patients during the Pandemic. Issue 5 (May 2023) - Stumbar, Sarah E.; Garba, Nana Aisha; Minor, Suzanne; Toonkel, Rebecca; Bonnin, Rodolfo; Obeso, Vivian
Abstract : In the coming decades, pandemics are likely to increase in frequency and severity. Therefore, the academic medicine community must learn from the COVID-19 pandemic to craft proactive, systematic strategies to ensure that medical students are trained in emerging diseases. This article outlines the process by which the authors' institution developed guidelines for student participation in the care of patients with COVID-19 and reports on students' experiences with these policies. Abstract: Objectives: Recent disease modeling suggests that pandemics are likely to increase in frequency and severity. As such, medical educators must learn from their experiences with coronavirus disease 2019 (COVID-19) to develop systematic strategies for ensuring that medical students receive hands-on training in the management of emerging diseases. Here, we outline the process by which the Florida International University Herbert Wertheim College of Medicine developed and updated guidelines for student participation in the care of patients with COVID-19 and report on students' experiences. Methods: During the 2020–2021 academic year, Florida International University Herbert Wertheim College of Medicine students were not permitted to care for patients with COVID-19; however, academic year 2021–2022 guidelines did permit fourth-year students on subinternships or Emergency Medicine rotations to voluntarily care for patients with COVID-19. At the end of the 2021–2022 academic year, students completed an anonymous survey about their experience caring for patients with COVID-19. Likert-type and multiple-choice questions were analyzed using descriptive statistics and the short-answer responses were analyzed qualitatively. Results: One hundred two students (84%) responded to the survey. Sixty-four percent of respondents opted to provide care for patients with COVID-19. Most students (63%) cared for patients with COVID-19 during their required Emergency Medicine Selective. Twenty-eight percent of students wished they had more COVID-19 patient care opportunities, and 29% did not feel prepared to care for patients with COVID-19 on their first day of residency. Conclusions: Many graduating students felt unprepared to care for patients with COVID-19 during residency and many wished they had had more opportunities to care for patients with COVID-19 during medical school. Curricular policies must evolve to allow students to gain competency in the care of patients with COVID-19 so that they are prepared for day one of residency.